Implementasi Langkah Kerja Konseling Model Kipas dalam Mengembangkan Karakter Generasi Alpha - Muhammad Nikman Naser; Syukri Hamzah; Andi Mappiare (Universitas Islam Negeri Madura, 2022)
KIPAS counseling is a counseling framework based on indonesia's cultural value system. The Alpha generation, which is quite unique today, requires BK teachers and stakeholders to always collaborate in building student character. The purpose of this study is to implement the steps of the KIPAS counseling work that are integrated in the learning process in schools. This research uses collaborative action research methods, namely researchers collaborating in the implementation of BK services that are integrated with school management and PBM. The study was conducted in 5 step cycles of activity. The results showed that after the implementation of the KIPAS counseling work step, it was seen that a progress was made in facilitating the development of student character